PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI (Studi Kasus Pada Bank Syariah Tahun 2015-2018) - rizky guntarto adit; Isnantyo Arief Nugroho (Universitas Muhammadiyah Prof Dr Hamka, 2020)
This study aims to determine the effect of Liquidity, Leverage, and Profitability on the disclosure of Islamic Social Reporting (ISR). Disclosure of Islamic Social Reporting (ISR) is measured using the ISR index. The population in this study is Sharia Banks in Indonesia in the 2015-2018 period. The total data used is 36 data from 9 samples of Islamic banks using purposive sampling. The results of this study indicate that Liquidity, Leverage, and Profitability towards the disclosure of Islamic Social Reporting. Keywords: Liquidity, Leverage, Profitability, Islamic Social Reporting (ISR)